Proceedings of the 5th International Conference on Education and Technology (ICET 2019) 2019
DOI: 10.2991/icet-19.2019.173
|View full text |Cite
|
Sign up to set email alerts
|

Educative Learning Media for Elementary School Students

Abstract: This research is motivated by using instructional media that is less appropriate in social study learning. The purpose of this study was to develop an Android-based educational learning media in social study learning for elementary school students. This research is development research using four D model. The results of this study show that the development of Android-based educational learning media for elementary students is valid, practical and effective. The implication of this research is it can be used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…The validation results of the questionnaire are thought to be due to the substance being able to see the practicality of the media being developed, through the formulation of statements that are in accordance with the objectives of the questionnaire, and in its construction the questionnaire was able to see the practicality of the media through the formulation of clear statements and complete ideas. This statement is in accordance with what was stated by Miaz et al (2019) that testing the practicality of educational learning media can be carried out using a questionnaire instrument given to practitioners (teachers) and students, where the instrument is in the form of a questionnaire which is distributed containing aspects of assessing the ease of use of the media. learning, benefits obtained from learning media, displays, and time used in learning activities when using learning media.…”
Section: Resultssupporting
confidence: 85%
“…The validation results of the questionnaire are thought to be due to the substance being able to see the practicality of the media being developed, through the formulation of statements that are in accordance with the objectives of the questionnaire, and in its construction the questionnaire was able to see the practicality of the media through the formulation of clear statements and complete ideas. This statement is in accordance with what was stated by Miaz et al (2019) that testing the practicality of educational learning media can be carried out using a questionnaire instrument given to practitioners (teachers) and students, where the instrument is in the form of a questionnaire which is distributed containing aspects of assessing the ease of use of the media. learning, benefits obtained from learning media, displays, and time used in learning activities when using learning media.…”
Section: Resultssupporting
confidence: 85%
“…They found that the use of technology in the instruction could motivate and improve students' learning process. Another study disclosed that the students who used android-based interactive multimedia would be better in their understanding the lesson (Humairah et al, 2020;Miaz et al, 2019). The mobile-learning also provided students' opportunities to acquire skills and use the best technological facilities in order to reach learning outcomes (Abd Samad et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan penelitian (Miaz, 2019) media pembelajaran yang edukatif dapat memberikan banyak manfaat dalam proses pembelajaran. Sejalan dengan itu, (Rosmiati, 2023) mengatakan bahwa media pembelajaran berbasis android memiliki banyak kelebihan.…”
Section: Pendahuluanunclassified